For Whom The Bell Tolls - Hemingway, Ernest (London ILQA Publication, 2017)
Taked with blowing up a bridge behind enemy lines, Jordan is distracted by partisan Maria at base camp, who catches his eye and his heart. As Jordan's love for Maria grows, he not only begins to question his assignment and his politics, but also his place in this foreign war far from home
Keywords: Spain -- Civil War (Spain : 1936-1939) -- War stories